Comparison and Analysis of the Performances and Mechanisms of Recycled Asphalt Incorporating High-Permeability Rejuvenating Agent - Yanjuan Tian; Mulian Zheng; Hailei Xu; Chupeng Chen; Jinhao Zhang (Advances in Civil Engineering, 2019)
The objective of this study is to develop a highly permeable rejuvenating agent for the recycling of the asphalt pavement. The rheological properties and permeability of recycled asphalt after adding the self-developed rejuvenating agent, as well as two other agents, were compared and evaluated. An improved softening point method was devised to evaluate the permeability. In addition, the recycled asphalt was analyzed using Fourier transform infrared spectroscopy (FTIR). The results showed that the self-developed rejuvenating agent had high permeability, could effectively restore the performance of the aged asphalt, and could improve the aging-resistant property of the recycled asphalt. FTIR analysis showed that the matrix asphalt experienced oxygen absorption and dehydrogenation during the aging process. The aging of the SBS-modified asphalt was achieved via dual aging of the matrix asphalt and SBS-modified components. In addition, the rejuvenating agent CA had an inhibitory effect on asphalt aging, and its recycling efficiency was better than that of the rejuvenating agent A for the aged SBS-modified asphalt. Finally, a relationship between the microscopic functional group index and the macroscopic test index was established.